Development and improvement of switching stands of high-voltage LUE modulators - Beloglazov, V.I.; Kosoy, O.I.; Mats, V.A.; Romasko, V.P.; Chertischev, I.A.; Tytov, V.Yu.; Chaika, I.O.; Titarenko, Yu.A.; Tur, Yu.D. (Вопросы атомной науки и техники, 2019)
The results of the development, operation and improvements of switch racks are presented. Particular attention is paid to the control and protection systems of both the thyratrons themselves and the control units of the switches. The main characteristics and the degree of reliability of switching racks and thyratrons of various types are compared. The development and implementation of switching racks based on six types of thyratrons was carried out: TGI1-1000/25, TGI1-2500/35, TGI1-5000/50, TGI1-5k/50 (Russia), TGI1-2500/50 (Ukraine) and CX 1525 A (England). Представлено результати розробок, експлуатації та удосконалень комутаційних стойок. Особливу увагу приділено системам контролю і захисту як самих тиратронів, так і управляючих блоків комутаторів. Проведено порівняння основних характеристик і ступеня надійності комутаційних стійок і тиратронів різного типу. Проведена розробка та впровадження комутаційних стойок на основі шести типів тиратронів: ТГІ1-1000/25, ТГІ1-2500/35, ТГІ1-5000/50, ТГІ1-5к/50 (Росія), ТГІ1-2500/50 (Україна) і СХ 1525 А (Англія). Представлены результаты разработок, эксплуатации и усовершенствований коммутационных стоек. Особое внимание уделено системам контроля и защиты как самих тиратронов, так и управляющих блоков коммутаторов. Проведено сравнение основных характеристик и степени надежности коммутационных стоек и тиратронов различного типа. Проведена разработка и внедрение коммутационных стоек на основе шести типов тиратронов: ТГИ1-1000/25, ТГИ1-2500/35, ТГИ1-5000/50, ТГИ1-5к/50 (Россия), ТГИ1-2500/50 (Украина) и СХ 1525 А (Англия).